Особенности трансформации клеток Erwinia carotovora плазмидой pECL18 - Черватюк, Н.В.; Товкач, Ф.И.; Горб, Т.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
Transformants Erwinia carotovora subsp. carotovora carrying pECL18 plasmid have been obtained with the help of the modified calcium method. The transformation frequency was 2.8 × 103 colonies per μg of plasmid DNA. It has been established that the calcium competence of E. carotovora could be obtained by subjecting the cell from the logarithmic phase of growth to 0.1 М CaCl2 per 5 × 108 cell/ml. The frequency of the spontaneous loss of pECL18 plasmid is less than 1%. The ability to restrict the phage reproduction and the nuclease synthesis by the transformants has been studied. Foreign and homing RM-systems are autonomous, i.e. inhibit the phage reproduction independently. The obtained data are the prerequisite to construct a biotechnological system on the basis of non-pathogenic E. carotovora.